Association of chronic opioid therapy and opioid use disorder with COVID-19-related hospitalization and mortality: Evidence from three health systems in the United States - Nguyen, Anh P.; Binswanger, Ingrid A.; Narwaney, Komal J.; Ford, Morgan A.; McClure, David L.; Rinehart, Deborah J.; Lyons, Jason A.; Glanz, Jason M. (Preventive medicine reports, 2024)
Chronic opioid use can lead to detrimental effects on the immune and various organ systems that put individuals prescribed chronic opioid therapy (COT) for pain and those with an opioid use disorder (OUD) at risk for severe COVID-19 disease. We assessed the association of COT and OUD with COVID-19-related hospitalization and death to inform targeted interventions to improve clinical outcomes in COVID-19 patients who use opioids. We conducted a retrospective cohort study of adults ages ≥ 18 with laboratory-confirmed SARS-CoV-2 infection in 2020 and 2021 from three US health systems. We used Cox proportional hazards regression to estimate the 30-day risk of COVID-19-related hospitalization and death associated with two opioid exposures (COT and OUD) following an infection. The study cohort included 53,123 patients with SARS-CoV-2 infection and a mean (SD) age of 45.1 (16.5), of whom 1,059 (2.0 %) were exposed to COT and 269 (0.5 %) had an OUD diagnosis in the year prior to infection. There were 2,270 observed COVID-19-related hospitalizations or deaths (1.6 per 1,000 person-days, 95 % CI 1.5–1.7). In the fully adjusted model, COT was not associated with increased risk (HR 1.19; 95 % CI, 0.98–1.43), while past-year OUD was independently associated with severe COVID-19 disease (HR 1.82; 95 % CI, 1.18–2.80). Past-year OUD remained associated with increased risk in post-hoc analysis with COVID-19-related hospitalization alone as the outcome (HR 2.00; 95 % CI, 1.30–3.08). Past-year OUD is a potential independent risk factor for severe COVID-19 disease that warrants monitoring to improve the prognosis of patients with COVID-19.